Conceptual bases for assessing and modeling sustainable development of a region as an ecological‐socio‐economic system (the example of the Republic of Dagestan) - M. M. Magomedova; U. A.-I. Kurbanova; K. D. Dakhdueva (Юг России: экология, развитие)
Aim. The aim of the research has been: the study of the conceptual foundations of sustainable development of the region, identification of the main factors, signs, patterns, principles, preconditions for sustainable development of the region as an ecological and socio‐economic system and the proposition of new approaches to the analysis, assessment and modeling of the development of the region from the standpoint of a systematic approach.Material and Methods. The research carried out by the authors was based on statistical data from the Federal State Statistics Service, characterising the ecological and socio‐economic development of the Republic of Dagestan. Analysis of the degree of influence and assessment of the prerequisites, factors, conditions of the ecological, socio‐economic development of the region made it possible to substantiate the choice of research methods, most of which are deterministic or probabilistically deterministic in the nature of information. In this regard, the study used methods of quantitative research, which are based on factorial, genetic and normative approaches, including methods of expert assessments, balance planning methods, economic and mathematical methods of optimization and assessment of economic efficiency.Results. The authors propose new approaches to the study of the problems of assessment, modeling and forecasting of the ecological, socio‐economic development of the region, which will make it possible to identify emerging trends that drive its development. Based on the research of indicators that characterise the basic and auxiliary processes in the region, life support processes and processes that hinder the development, an assessment of the quantitative transformations of ecological‐socio‐economic development in Dagestan was carried out. Conclusion. The methodology used made it possible to obtain a qualitative characteristic of the regional space to analyze and assess the transformation processes in the ecological‐socio‐economic development of the Republic of Dagestan and to provide an integrated assessment of regional processes.